2009
DOI: 10.7771/1541-5015.1088
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Summarizing Findings and Looking Ahead to a New Generation of PBL Research

Abstract: The articles in this issue eff ectively summarize three decades of Problem Based Learning (PBL) research. The meta-analysis (Walker & Leary) and meta-synthesis (Strobel & van Barneveld) articles review outcomes of studies conducted from 1976 to 2007 that compared a PBL curriculum to a traditional curriculum. The third article off ers a critique of assessments used in these studies. This commentary highlights the conclusions of the articles and their unique contributions to our understanding of PBL and the brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 20 publications
1
43
0
5
Order By: Relevance
“…Notably, faculty in this study tended to engage discipline-specific community partners who became clients of the students. This finding begins to answer Ravitz's (2009) call for more research on how PBL is used across disciplines in higher education. As indicated by Dr. English, Dr. Education A, and Drs.…”
Section: Use Of Community Partners In Higher Educationmentioning
confidence: 83%
See 2 more Smart Citations
“…Notably, faculty in this study tended to engage discipline-specific community partners who became clients of the students. This finding begins to answer Ravitz's (2009) call for more research on how PBL is used across disciplines in higher education. As indicated by Dr. English, Dr. Education A, and Drs.…”
Section: Use Of Community Partners In Higher Educationmentioning
confidence: 83%
“…While Ward and Lee (2002) noted that the philosophies supporting PBL are well established, they complain that the "how-to's are in short supply" (p. 21). Ravitz (2009) suggested that scholars should investigate how PBL is used across disciplines, as well as the effectiveness of particular PBL practices and processes. He also recommended that studies not draw a false dichotomy between PBL and traditional instruction.…”
Section: Pbl In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one article was the result of cross-country collaboration (see Skinner, Braunack-Mayer, & Winning, 2015). We are pleased to see that all these articles demonstrate an effort to move away from if to how as we look forward to a new generation of PBL research (Ravitz, 2009), that is, from investigating if PBL works to exploring ways to design effective PBL curricula and experiences, motivate and help students to learn in the PBL environment, prepare faculty for successful PBL implementation, assess diverse learning processes and outcomes, and augment PBL with learning technologies. Furthermore, we are impressed by a variety of theoretical lenses (e.g., motivation, critical theory) and research methods (e.g., structural equation modeling, case study, interactional ethnography) represented in this special issue.…”
Section: Purpose and Overviewmentioning
confidence: 99%
“…Because students develop their own path to solve the ill-structured task, their activities become meaningful as they work to meet the project goals and ultimately the learning objectives (Pedersen & Liu, 2003). PBL shows promise in a number of disciplines such as science, engineering, teacher education, social science, and business (Ravitz, 2009). Despite the recognized benefits and effectiveness of PBL, using PBL in K-12 education is difficult and, therefore, relatively uncommon (Ertmer & Simons, 2006;Hmelo-Silver, 2004).…”
Section: Pbl and Its Affordancesmentioning
confidence: 99%